Feeding Rates of Black Soldier Fly (Hermetia Illucens) Fed on Palm Kernel Meal and Bovine Blood - Susanti, Rina; Ramadhani Eka Putra, (Jurnal Biodjati, 2025)
Slaughterhouses are economic activities that generate significant waste, including blood. Blood is a biological hazardous material due to its potency as a source of disease. Standard waste management methods for this material, involving physical and chemical treatment technologies, are considered expensive and impractical for small-scale entrepreneurs, leading to a neglect of waste management. Another possible waste management approach for blood is to use biological agents that utilize its nutrients. One candidate is the black soldier fly, known for its ability to consume various organic materials to produce high-value biomass. However, this process is highly dependent on the feed material's characteristics and the feeding rate. In this study, bovine blood was mixed with fermented palm kernel meal as the feeding material for black soldier fly (Hermetia illucens) larvae. The objective of this study was to assess the effect of feeding rates of 50, 100, 200, 300, and 400 mg/larvae/day on the growth performance and survival of the larvae. The results showed that the time required for larvae to become pupae is 20-24 days. A 200 mg/larvae/day produced the best harvested weight and lowest FCR (feed conversion ratio). The highest growth rate was achieved at a dosage of 300 mg/larvae/day. At the same time, a 400 mg/larvae/day dose produced the highest length and WRI (Waste Reduction Index). On the other hand, the survival rate ranged from 77% to 91%, with 100 mg/larvae/day being the most effective. Mixing bovine blood with palm kernel meal at a feeding rate of more than 100 mg/larvae/day will allow the effective black soldier fly (H. illucens) larval composting process.